Lewis Milestone : Life and Films - Robinson, Harlow (Book collections on Project MUSE., 2019)
"As a young boy growing up in a small Russian/Ukranian city to a family of Jewish heritage, Lewis Milestone (1895-1980) witnessed the violence of the anti-semitic pogroms during the Revolution of 1905. Years later, Milestone served the United States military in World War I, and lived through Word War II, the Korean War, and the Cold War, giving him personal experience with the devastation of military combat. Although he initially dreamed of working in the theater, Milestone moved to Hollywood in 1919. He first worked as a film cutter and then later signed with Howard Hughes in 1926 where he quickly rose to prominence in the film world as a director. The bitter and destructive ideological conflicts of the twentieth century impacted Milestone, and began to resonate in his varied body of work. One of the most productive directors of his era, Milestone completed thirty-eight films in thirty-seven years, and during this period film underwent unprecedented technological changes. Milestone adapted easily in the transition from silent, black and white films to color and sound, creating classics such as Two Arabian Knights (1927), All Quiet on the Western Front (1930), and Of Mice and Men (1939). He worked with countless stars such as Gary Cooper, Joan Crawford, Bing Crosby, Ginger Rogers, and Kirk Douglas. Milestone's story is a classic rags-to-riches American narrative, starting with humble beginnings and eventually leading to Hollywood, where he directed some of the most innovative and influential anti-war films ever created during an era where talent and hard work mattered much more than pedigree. Lewis Milestone: Life and Films examines Milestone's life and career and will evaluate his films thematically and technically, paying special attention to his method of adapting literary works into screenplays and the currently underappreciated use of music in his films. Film historians and critics regard Lewis Milestone as one of the major directors of the Golden Age of Hollywood, but his long, remarkable, and influential career has not received the scholarly attention it deserves. Lewis Milestone seeks to give the director the credit he earned in the American film canon"--